2020
DOI: 10.1159/000508783
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Cryptococcosis: An Unusual Injection Site Infection

Abstract: Primary cutaneous cryptococcosis (PCC) is an uncommonly reported entity. We describe an unusual case of PCC in an injection site of an immunocompromised patient. The specific case demonstrates a challenging treating dilemma with different alternative treatment choices. In the presented clinical setting, each choice concealed its risks and benefits. We highlight the importance of patient education for taking the appropriate measures for the disinfection of subcutaneous injection sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Kronstand, et al, reported that a high fungal load, to which the host is exposed, can explain the disease in immunocompetent persons, via the inhalation of a large number of infectious spores [17]. However, the route of exposure via traumatic inoculation seems more strongly related to PCC [4,16,[18][19][20]. Since the habitat of pigeons and other birds is a reservoir for Cryptococcus species in the environment, we believe this mycosis resulted from an occupational exposure in our case, as has already been described in the literature [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Kronstand, et al, reported that a high fungal load, to which the host is exposed, can explain the disease in immunocompetent persons, via the inhalation of a large number of infectious spores [17]. However, the route of exposure via traumatic inoculation seems more strongly related to PCC [4,16,[18][19][20]. Since the habitat of pigeons and other birds is a reservoir for Cryptococcus species in the environment, we believe this mycosis resulted from an occupational exposure in our case, as has already been described in the literature [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…1 Skin lesions in cutaneous cryptococcosis are cysts, acneiform papules, pustules, nodules, molluscum contagiosum like umbilicated lesions and necrotizing fasciitis. 4 Systemic dissemination from primary cutaneous cryptococcosis is extremely rare. In a series of 22 cases of primary cutaneous cryptococcosis described by Neuville et al one patient co-infected with HIV had cryptococcal antigens in CSF.…”
Section: The Natural Course Of the Disease Clinical Features And Hist...mentioning
confidence: 99%
“…[1][2][3] Cutaneous infections are the third most common clinical manifestation of cryptococcosis, and these patients can present with various skin aberrations such as, papules, nodules, tumors, ulcerations, ecchymoses, pustules, abscesses and granulomas. [4][5][6][7] Early identification of polymorphic skin manifestations and treatment are essential for an effective prognosis of the infection. This condition can be divided into primary and secondary cutaneous cryptococcosis.…”
Section: Introductionmentioning
confidence: 99%